VISCOSITY AND PARTICLE SIZE DISTRIBUTION OF CONCENTRATED APPLE JUICE PRODUCED BY SPINNING DISC REACTOR (SDR) - Novi Safriani (Jurnal Teknologi dan Industri Pertanian Indonesia, 2012)
This research  explored the potential use of the spinning disc reactor (SDR), a novel processing technique used for the production of concentrated apple juice. The apple juice was passed over the SDR disc spinning at 2000 rpm, heated at various temperatures (90 °C, 100 °C, 110 °C, and 120 °C), and at a flow rate of 7 ml/s. The effect of SDR-processing on viscosity and particle size of the apple juice concentration,  was investigated. The SDR-concentrated apple juice exhibits narrow particle size distribution (average particle size in the range of d32 = 0.1-0.2 µm and d43 = 4-12 µm) and shear-thinning behaviour in the range of shear rates from 0.1 – 200 s-1, in which the viscosity decreases with increasing the shear rate. The reconstituted samples show  similar viscosity with its original counterpart.  The increase of the processing temperature allows a reduction in the processing time. The results reveal that the SDR is capable of producing the concentrated apple juice.